Anchoring and Catalytic Performance of Co@C2N Monolayer for Rechargeable Li-SexSy Batteries: A First-Principles Calculations - Xiaojing Li; Yingbo Zhang; Chenchen Liu; Shuwei Tang (Molecules)
SexSy composite cathode materials, which offer superior theoretical capacity compared to pure selenium and improved electrochemical properties relative to pure sulfur, have aroused considerable interest in recent decades on account of their applications in electric vehicles and energy storage grids. In the current work, the feasibility of a Co@C2N monolayer as a promising host candidate for the cathode material of Li-SexSy batteries has been evaluated using first-principles calculations, and particular efforts have been devoted to underscoring the anchoring mechanism and catalytic performance of the Co@C2N monolayer. The pronounced synergistic effects of Co-S and Li-N bonds lead to increased anchoring performance for Li2SexSy/SexSy clusters on the surface of Co@C2N monolayer, which effectively inhibit the shuttle effect. The charge density difference and Mulliken charge analysis underscores a substantial charge transfer from the Li2SexSy and SexSy clusters to the Co@C2N monolayer, which indicates a noticeable chemical interaction between them. Further electronic property calculations show that the Co@C2N monolayer can improve the electrical conductivity of cathode materials for Li-SexSy batteries by maintaining semi-metallic characteristics after anchoring of Li2SexSy/SexSy clusters. Additionally, the catalytic performance of the Co@C2N monolayer is evaluated in terms of the reduction pathway of Se8 and the decomposition energy barrier of the Li2SeS cluster, which highlights the catalytic role of the Co@C2N monolayer in the formation and decomposition of the Li2SeS cluster during the cycle processes. Overall, the Co@C2N monolayer emerges as a promising host material and catalyst for Li-SexSy batteries with remarkable anchoring and catalytic performance.